ANALISIS NILAI-NILAI KARAKTER DALAM KEGIATAN NYABA KA LEMBUR DI RA AL-BIRUNI MAJALENGKA(Studi Kasus di RA Al-Biruni Majalengka) - Dhanty Damayanti, - (2022)
Create to the next generation with good character and personality can fostered early. early childhood 25 percent group of individuals in society, but 100 percent of the future. So to create superior society, started by forming generation of children who have a strong culture and character. Living in a community means children grow and develop in an environment, at school, family, and community. The environment is main factor in the formation of child's character, hoped that the child get a good stimulus example from the surrounding environment. The result child has a good character. Then children have a sense of care for environment, protect environment and are able to preserve the culture in their environment such as language and other cultures as local wisdom in their environment. The purpose of this study was to determine the value of children's character in nyaba ka lembur. Research uses qualitative approach with a case study method. Resource in this study were principals and teachers at RA Al-Biruni Majalengka. Collecting data using direct observation techniques, interviews and documentation. Based the results of observations and data processing, it is known that nyaba ka lembur, children's character values are obtained, namely cultural values and social values.